The Optimal Rate of Money Creation in an Overlapping Generations Model : Numerical Simulations for the U.S. Economy - Hamann, A. (IMF Working Papers; Working Paper ;, 1992)
This paper develops a large scale overlapping generations model and calibrates it for the U.S. economy. Simulations with the model show that the steady state welfare maximizing inflation rate may be positive, although the numerical results are not robust. It is also shown, however, that increases in the inflation rate are never Pareto efficient because during the transition to the new steady state at least some generations are made worse-off. Using an optimality criterion that takes into account the welfare of all generations, it is found that implementing Friedman's rule is a Pareto superior policy, and that the efficiency gains derived from implementing such rule could be substantial.